HClO-Activated Fluorescence and Photosensitization from an AIE Nanoprobe for Image-Guided Bacterial Ablation in Phagocytes - Wu, Min (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 Wiley-VCH GmbH.